2016
DOI: 10.1155/2016/7950374
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Admission Base Deficit Is Associated with a Complex Dynamic Network of Systemic Inflammation Which Drives Clinical Trajectories in Blunt Trauma Patients

Abstract: We hypothesized that elevated base deficit (BD) ≥ 4 mEq/L upon admission could be associated with an altered inflammatory response, which in turn may impact differential clinical trajectories. Using clinical and biobank data from 472 blunt trauma survivors, 154 patients were identified after excluding patients who received prehospital IV fluids or had alcohol intoxication. From this subcohort, 84 patients had a BD ≥ 4 mEq/L and 70 patients with BD < 4 mEq/L. Three samples within the first 24 h were obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 74 publications
1
17
0
Order By: Relevance
“…P < 0.05 was considered statistically significantly different for all analyses. Dynamic Network Analysis (DyNA) was performed to gain insights into the temporal dynamic changes in network connectivity of the post-traumatic inflammatory response [as we have shown previously (8, 21,25)] among the FCM-defined clusters.…”
Section: Discussionmentioning
confidence: 99%
“…P < 0.05 was considered statistically significantly different for all analyses. Dynamic Network Analysis (DyNA) was performed to gain insights into the temporal dynamic changes in network connectivity of the post-traumatic inflammatory response [as we have shown previously (8, 21,25)] among the FCM-defined clusters.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to our previously cited studies, our work using multiplex assays has highlighted how differences in clinical presentation relate to biomarker concentrations postinjury. A 2016 study found that patients with elevated base deficit (≥4 mEq L −1 ) upon arrival had significant elevations of a subset of mediators of the innate and lymphoid responses . Similarly, we investigated 22 patients who sustained hypotension in the prehospital setting and were matched (based on sex ratio, age and ISS) with 28 normotensive patients.…”
Section: Insights From Large Prospective Studies Of the Post‐traumatimentioning
confidence: 99%
“…The data‐driven tool that has proven most useful in leading to mechanistic hypotheses in both experimental and human trauma has been Dynamic Network Analysis (DyNA) due to the fact that it allows for a granular view of putative interconnected inflammatory cascades over defined time intervals following injury . This algorithm has allowed us to identify key differences between experimental haemorrhagic shock vs. sham in mice ; to implicate type 17 immunity as an early mechanism characterizing the systemic inflammatory responses of trauma nonsurvivors vs. highly matched survivors ; and to define divergent dynamic patterns of network complexity in trauma patients who develop nosocomial infection vs. controls .…”
Section: Computational Tools For Biomarker Analysismentioning
confidence: 99%
“…In the context of the acute inflammatory response, DyNA can help suggest how these networks of inflammatory mediators change in complexity or connectively over certain time intervals. Examples of the utility of DyNA for critical illness include defining key structural differences in the inflammatory responses of mice undergoing trauma/haemorrhage vs. trauma alone [47]; the finding that human blunt trauma non-survivors [*11] as well as PALF non-survivors [54] exhibit dynamic networks that suggest ever-amplifying inflammation; the finding that the chemokine MCP-1/CCL2 is a central driver of stress induced hepatocyte inflammation in vitro [55]; and the demonstration of divergent inflammatory responses in various subsets of highly matched trauma patients [56, 57]. …”
Section: Important Developments In Computational and Modelling Approamentioning
confidence: 99%